EXPERIMENTAL TEST-BENCH FOR RESEACHING PROPERTIES OF FUEL-LUBRICANT MATERIALS - Puzik Оleksii; Zaionchkovskyi, Gennadii; Tarasenko, Taras (Proceedings of National Aviation University (archive), 2013)
Was founded that problem of cavitation technologies based on throttles is little known. Proposed designed and produced experimental test-bench for using, which can exploited for diagnostics properties of working fluids through the analysis of cavitation pressure fluctuations.